Tratamento farmacológico da doença de buerger: revisão sistemática com metanálise - Cacione, Daniel Guimaraes [UNIFESP] (2016)
Objective: To assess the effectiveness of any pharmacological agent (intravenous or oral) compared with placebo or any other pharmacological agent in patients with Buerger's disease. Methods: A Cochrane systematic review was done. The Cochrane Vascular Trials Search Co-ordinator searched their Specialised Register (last searched in April 2015) and the Cochrane Register of Studies (Issue 3, 2015). The review authors searched trial registers and the European grey literature; screened reference lists of relevant studies, and contacted study authors and major pharmaceutical companies. Selection criteria was randomised controlled trials (RCTs) involving pharmacological agents used in the treatment of Buerger's disease. Two review authors, independently assessed the studies, extracted data and performed data analysis. Results: Five randomised controlled trials (total 602 participants) compared prostacyclin analogue with placebo, aspirin, or a prostaglandin analogue, and folic acid with placebo. No studies assessed other pharmacological agents such as cilostazol, clopidogrel and pentoxifylline or compared oral versus intravenous prostanoid.Compared with aspirin, intravenous prostacyclin analogue iloprost improved ulcer healing (risk ratio (RR) 2.65; 95% confidence interval (CI) 1.15 to 6.11; 98 participants; one study; moderate quality evidence), and helped to eradicate rest pain after 28 days (RR 2.28; 95% CI 1.48 to 3.52; 133 participants; one study; moderate quality evidence), although amputation rates were similar six months after treatment (RR 0.32; 95% CI 0.09 to 1.15; 95 participants; one study; moderate quality evidence). When comparing prostacyclin (iloprost and clinprost) with prostaglandin (alprostadil) analogues, ulcer healing was similar (RR 1.13; 95% CI 0.76 to 1.69; 89 participants; two studies; I² = 0%; very low quality evidence), as was the eradication of rest pain after 28 days (RR 1.57; 95% CI 0.72 to 3.44; 38 participants; one study; low quality evidence), while amputation rates were not measured. Compared with placebo, the effects of oral prostacyclin analogue iloprost were similar for: healing ischaemic ulcers (iloprost 200 mcg: RR 1.11; 95% CI 0.54 to 2.29; 133 participants; one study; moderate quality evidence, and iloprost 400 mcg: RR 0.90; 95% CI 0.42 to 1.93; 135 participants; one study; moderate quality evidence), eradication of rest pain after eight weeks (iloprost 200 mcg: RR 1.14; 95% CI 0.79 to 1.63; 207 participants; one study; moderate quality evidence, and iloprost 400 mcg: RR 1.11; 95% CI 0.77 to 1.59; 201 participants; one study; moderate quality evidence), and amputation rates after six months (iloprost 200 mcg: RR 0.54; 95% CI 0.19 to 1.56; 209 participants; one study, and iloprost 400 mcg: RR 0.42; 95% CI 0.13 to 1.31; 213 participants; one study). When comparing folic acid with placebo in patients with Buerger's disease and hyperhomocysteinaemia, pain scores were similar, there were no new cases of amputation in either group, and ulcer healing was not assessed (very low quality evidence).Treatment side effects such as headaches, flushing or nausea were not associated with treatment interruptions or more serious consequences. Outcomes such as amputation-free survival, walking distance or pain-free walking distance, and ankle brachial index were not assessed by any study. Overall, the quality of the evidence was very low to moderate, with few studies, small numbers of participants, variation in severity of disease of participants between studies and missing information regarding for example baseline tobacco exposure. Conclusions moderate quality evidence suggests that intravenous iloprost (prostacyclin analogue) is more effective than aspirin for eradicating rest pain and healing ischaemic ulcers in Buerger's disease, but oral iloprost is not more effective than placebo. Verylow and low quality evidence suggests there is no difference between prostacyclin (iloprost and clinprost) and the prostaglandin analogue alprostadil for healing ulcers and relieving pain respectively in severe Buerger's disease. Very-low quality evidence suggests there is no difference in pain scores and amputation rates between folic acid and placebo, in people with Buerger's disease and hyperhomocysteinaemia. High quality trials assessing the effectiveness of pharmacological agents (intravenous or oral) in people with Buerger's disease are needed.